2019
DOI: 10.1111/bju.14676
|View full text |Cite
|
Sign up to set email alerts
|

Use of the IDEAL framework in the urological literature: where are we in 2018?

Abstract: ObjectivesTo assess uptake and application of the IDEAL principles in original surgical procedure-or device-related clinical research studies, as well as its reported relevance as characterized by secondary publications, editorials and reviews. ConclusionsThe IDEAL framework has found widespread adoption in the urology literature as witnessed by a large number of original manuscripts and secondary publications citing IDEAL; however, its application is largely limited to the early stages of surgical innovation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…Following deduplication and abstract review, 51 relevant articles were identified. Thereafter remained fourteen primary papers [ 8 , 17 , 20 , 26 , 33 , 34 , 37 , 39 , 46 , 51 , 55 , 58 – 60 ], and 37 secondary papers [ 1 5 , 9 12 , 14 16 , 23 , 27 , 29 32 , 35 , 36 , 38 , 40 , 43 45 , 47 50 , 52 54 , 57 , 62 , 64 – 66 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Following deduplication and abstract review, 51 relevant articles were identified. Thereafter remained fourteen primary papers [ 8 , 17 , 20 , 26 , 33 , 34 , 37 , 39 , 46 , 51 , 55 , 58 – 60 ], and 37 secondary papers [ 1 5 , 9 12 , 14 16 , 23 , 27 , 29 32 , 35 , 36 , 38 , 40 , 43 45 , 47 50 , 52 54 , 57 , 62 , 64 – 66 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The remaining papers identified are consist of 10 letters to the editor (27%) [ 2 4 , 12 , 23 , 32 , 36 , 47 , 50 , 54 ], 2 questionnaire-based analyses (one exploring views on the use of evidence-based medicine principles in neurosurgery, the other seeking to understand the neurosurgical definition of “innovation”) [ 62 , 65 ], and 1 article outlining the work of the British Neurosurgical Trainee Collaborative [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although widely accepted in principle, the use of the IDEAL recommendations in practice to date has been limited and in many cases sub-optimal. Surveys of publications using IDEAL have shown that reporting of the stages was often inaccurate and the key features which define each stage were frequently omitted 7,8,9 . The IDEAL Recommendations introduce several novel ideas into clinical study design, and following other published guidelines alone is therefore unlikely to enable authors to report them accurately.…”
Section: Introductionmentioning
confidence: 99%